2021
DOI: 10.3390/coatings11121535
|View full text |Cite
|
Sign up to set email alerts
|

On the Etching Mechanism of Highly Hydrogenated SiN Films by CF4/D2 Plasma: Comparison with CF4/H2

Abstract: With the increasing interest in dry etching of silicon nitride, utilization of hydrogen-contained fluorocarbon plasma has become one of the most important processes in manufacturing advanced semiconductor devices. The correlation between hydrogen-contained molecules from the plasmas and hydrogen atoms inside the SiN plays a crucial role in etching behavior. In this work, the influences of plasmas (CF4/D2 and CF4/H2) and substrate temperature (Ts, from −20 to 50 °C) on etch rates (ERs) of the PECVD SiN films we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 52 publications
(84 reference statements)
0
3
0
Order By: Relevance
“…Negative ions appear in many gases that are often used in plasma technologies. Fluorine-containing gases (Carbon tetrafluoride CF 4 , Sulfur hexafluoride SF 6 and others) are widely used not only for etching different materials [1][2][3][4][5], but also for different plasma treatments of polymers' surfaces with the aim of changing their wetting properties, surface cleaning and activation before metal or paint layer deposition, for controlling their biocompatibility, chemical resistance [6][7][8][9][10], polymer film deposition [11], etc. Therefore our university students who study elementary processes in plasmas and plasma technologies carry out a set of undergraduate laboratory works.…”
Section: Introductionmentioning
confidence: 99%
“…Negative ions appear in many gases that are often used in plasma technologies. Fluorine-containing gases (Carbon tetrafluoride CF 4 , Sulfur hexafluoride SF 6 and others) are widely used not only for etching different materials [1][2][3][4][5], but also for different plasma treatments of polymers' surfaces with the aim of changing their wetting properties, surface cleaning and activation before metal or paint layer deposition, for controlling their biocompatibility, chemical resistance [6][7][8][9][10], polymer film deposition [11], etc. Therefore our university students who study elementary processes in plasmas and plasma technologies carry out a set of undergraduate laboratory works.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the molecular emission bands, e.g. , CF and CF 2 , are mainly located in the UV range and are not typically visible due to the spectral range chosen in this work and the fact that HF bands are typically not observable in OES measurement in the HF-containing plasmas. A clear dominance of Ar peaks (even with the 4% Ar admixture used in this study) allowed us to construct multiple actinometric ratios for calculating the F atom density, as presented below.…”
Section: Resultsmentioning
confidence: 99%
“…Simultaneously, the Si material undergoes oxidation and becomes passive by converting into SiOF . It has also been reported that high SiN/SiO 2 selectivity can be achieved using gas mixtures such as NF 3 /O 2 or CF 4 /N 2 /O 2 plasmas, which is attributed to the influence of NO radicals. , The addition of hydrogen to fluorocarbon gas, leading to the generation of CH x F y ions, can be used to enhance the etch rate (ER) and/or selectivity of SiN/SiO 2 or SiN/Si. Special hydrofluorocarbon gases have been used to achieve high etch selectivity for SiN over SiO 2 and Si. Additionally, the dependence of selectivities between Si-based materials on substrate temperature has recently been investigated by various research groups. , In hydrogen-contained fluorocarbon plasmas, the formation of hydrogen fluoride (HF) is anticipated to have a detrimental effect on etching for Si-based materials, as it tends to scavenge F radicals . In the mechanism of SiN etching, the H also reacts with N and CF x species, resulting in the formation of HCN as a byproduct, which helps to reduce the FC polymerization and facilitates the progress of SiN etching. , Based on the experimental and simulation results, it has been reported that HF molecules appear to play an important role in the selective etching of SiN over SiO 2 in NF 3 /N 2 /O 2 /H 2 remote plasmas , On the other hand, recently, there have been investigations into the selective etching of SiO 2 over SiN or Si using an HF vaper, employing both computational simulations and experimental approaches. , …”
Section: Introductionmentioning
confidence: 99%